Inheritance practices and gender differences in poverty and well-being in rural Ethiopia - Kumar, Neha; Quisumbing, Agnes R. (Wiley, 2012)
This article examines the role of men's and women's asset inheritance in poverty and well‐being in rural Ethiopia. Data from the Ethiopian Rural Household Survey (1997, 2004, and 2009) are used to investigate the following. (i) What is the long‐term impact of gender differentials in inheritance on household consumption, poverty and food security? (ii) Are there significant differences in poverty and well‐being between male‐and female‐headed households? The most important finding is that it is the amounts of inheritance received, and not whether women inherit at all, that have the most profound impacts. The area of land inherited is particularly important for women's long‐term well‐being. These findings underscore the importance of women's rights to inherit equally with men.